The Design Trends of Keystream Generator for Stream Cipher for High Immunity Attacks - Mostafa, Saifuldun; Saad, Hayder; Mustafa, Musa Jaber; Ali, Mohammed Hasan; Dhafer, Karam (Springer International Publishing, 2016)
Due to the latest changes in observing the external network related threats within the stream cipher, it become necessary to address these threats in order to identify the generator suitable for avoiding such threats. In this paper, the researcher addresses the current threats of immunity attacks in the stream cipher. Such attacks are resulted from the correlation within the key stream’s multiplexer. The key stream generators are also introduced in order to clarify its working process in avoiding attacks. After all, a comparison of key stream generators are resulted where it can be used as guidelines for other researches in designing key stream generator for high immunity attacks in the cipher.